CONSIDERATIONS RELATED TO ECONOMIC EFFICIENCY INDICES IN CASE OF ENERGY AUDIT FOR BUILDINGS - NAGHIU GEORGE SEBASTIAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
In the paper are presented the economic criteria on the basis of which the choice of selection of energetics modernization measures of existing buildings is made. The paper describes a synthesis of economic criteria from Romania and abroad on the basis of which the choice of technical solutions concerning the energetics modernization of existing buildings is made. Based on the article’s conclusions, one can make proposals aimed at improving the legislation presently in force in this field.